Analysis of Problem Solving in Islamic Boarding Schools Perspective of Islamic Psychology in the book "Collection of Exemplary Stories" by Hasballah Thaib and Zamakhsyari Hasballah - Siti Sopiah Maviani (al-Afkar, Journal For Islamic Studies, 2023)
There are educational components that are interrelated and needed in the learning process including teachers, students, employees, ways of educating, infrastructure, environment, vision and mission, evaluation and so on with the aim of creating effective learning. Therefore, problem solving is a learning method that encourages students to utilize ideal mindsets. This study used a qualitative method with a library research approach. Data collection techniques using documentation. The data sources for this research are books and journals related to Problem Solving learning in Islamic boarding schools and the development of psychological theories. With this research, it is hoped that students will be more effective in learning, namely being able to play an active role in the learning given by the teacher. Students actively voice ideas and think critically. With that problems can be solved.